RNA-Seq Reveals Enhanced Sugar Metabolism in Streptococcus mutans Co-cultured with Candida albicans within Mixed-Species Biofilms - He, Jinzhi; Kim, Dongyeop; Zhou, Xuedong; Ahn, Sang-Joon; Burne, Robert A.; Richards, Vincent P.; Koo, Hyun (Frontiers in Microbiology, 2017)
Early childhood caries (ECC), which can lead to rampant tooth-decay that is painful and costly to treat, is one of the most prevalent infectious diseases affecting children worldwide. Previous studies support that interactions between Streptococcus mutans and Candida albicans are associated with the pathogenesis of ECC. The presence of Candida enhances S. mutans growth, fitness and accumulation within biofilms in vitro, although the molecular basis for these behaviors is undefined. Using an established co-cultivation biofilm model and RNA-Seq, we investigated how C. albicans influences the transcriptome of S. mutans. The presence of C. albicans dramatically altered gene expression in S. mutans in the dual-species biofilm, resulting in 393 genes differentially expressed, compared to mono-species biofilms of S. mutans. By Gene Ontology analysis, the majority of up-regulated genes were related to carbohydrate transport and metabolic/catabolic processes. KEGG pathway impact analysis showed elevated pyruvate and galactose metabolism, suggesting that co-cultivation with C. albicans influences carbohydrate utilization by S. mutans. Analysis of metabolites confirmed the increases in carbohydrate metabolism, with elevated amounts of formate in the culture medium of co-cultured biofilms. Moreover, co-cultivation with C. albicans altered transcription of S. mutans signal transduction (comC and ciaRH) genes associated with fitness and virulence. Interestingly, the expression of genes for mutacins (bacteriocins) and CRISPR were down-regulated. Collectively, the data provide a comprehensive insight into S. mutans transcriptomic changes induced by C. albicans, and offer novel insights into how bacterial–fungal interactions may enhance the severity of dental caries.